Integrating Disability, Transforming Feminist Theory - Garland-Thomson, Rosemarie (NWSA Journal, 2002)
This essay aims to amplify feminist theory by articulating and fostering feminist disability theory. It names feminist disability studies as an academic field of inquiry, describes work that is already underway, calls for needed study and sets an agenda for future work in feminist disability studies. Feminist disability theory augments the terms and confronts the limits of the ways we understand human diversity, the materiality of the body, multiculturalism, and the social formations that interpret bodily differences. The essay asserts that integrating disability as a category of analysis and a system of representation deepens, expands, and challenges feminist theory. To elaborate on these premises, the essay discusses four fundamental and interpenetrating domains of feminist theory: representation, the body, identity, and activism, suggesting some critical inquiries that considering disability can generate within these theoretical arenas.
Keywords: EDI; activisme; approches et analyses; corps; cours; discipline; militance; premier cycle; queer; ressource en ligne; santé; sciences humaines; sciences sociales; sex1920; thématiques; études critiques du handicap; études féministes

Pour un regard féministe matérialiste sur le queer. Échanges entre une féministe radicale et un homme anti-masculiniste - Masson, Sabine; Thiers-Vidal, Léo (Mouvements, 2002)
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; cours; discipline; féminisme matérialiste; philosophie politique; pol4212; premier cycle; périodes historiques; queer; sciences humaines; sociologie; thématiques

Sexualities : Sexualities and their futures - Plummer, Kenneth (Critical concepts in sociology, 2002)
Bringing together classic writings on sexuality from a social science perspective, this fascinating set covers topics including the history of the study of the area, theoretical approaches and issues of gender and sexuality. Volume four considers the wider issues around sexualities - addressing social change, postmodernity and the shifting of sexualities, and presenting an examination of the term 'queer'. An epilogue of suggested further reading is also included.
Keywords: approches et analyses; discipline; genre; postmodernisme; queer; sciences humaines; sexualité; sociologie; thématiques